The EXERCISE INCREASES BRAIN-DERIVED NEUROTROPHIC FACTOR LEVEL ON PARKINSON’S DISEASE - Stefani Krisanti; Jeane Cynthia Wongso; Clara Angelia; Yuki Octavia Wijaya; Alice Angelina Surya Perdana (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2022)
With the current development of medical science today, anti aging medicine has developed rapidly, including in neuroscience aspect. Indicator of healthy aging is to maintain a good quality of life, include maintaining optimal brain function. One of lifestyle factors that can improve health, prevent chronic diseases, and maintain cognitive function is exercise. Exercise has been shown to increase brain-derived neurotrophic factor (BDNF), which acts as a biomarker of neuroprotective. In patients with Parkinson's disease was found a decrease in BDNF serum levels. BDNF plays a major role as neuroprotection and neurorestoration, its levels can be increased through regular exercises with moderate-intensity. Thus, it can be considered as adjunctive therapy in Parkinson's disease. This literature review is to explain the correlation between exercise and BDNF level in Parkinson’s Disease.